Betesdrift för mjölkkor - Jönsson, Emma (2005)
The Swedish Animal Welfare Act say that all milking cows must have access to pasture in summer time. That was a gift to Astrid Lindgren o her 80th birthday from the Swedish Government. Sweden is a predecessor in animal welfare, but how well do we live up to these big expectations? In this thesis I will examine how well the pasture for milking cows works. I have been interviewing farmers with milking cows and people in the business. I have also been searching information on Internet, and using the library of Alnarp. Cows that are kept on pasture are exposed to different kind of parasites, but on the other hand they run a smaller risk to getting acetonemi, pareses and udder infection. Veterinary Pierre Nordmark means that cows on pasture are more healthy then cows kept inside all summer. Inside the stable the concentration of an infection is higher. In that way infections are easily spread. It is hard to achieve a good climate in the stable during summer time. One thing that is bad whit pasture is that the cows are exposed to big changes. The cows can get rumen disorders. You should not let out the cows if there is a risk to their health the veterinary says. He also says that most of the cows in his district are kept outside in the summer time. However, cows are not on pasture the prescribe time. Swedish Animal welfare Agency in Skara is approving exemptions. It is very hard to get an exemption. Last year only 10 farmers received exemption. To get an exemption you have to profile certain demands. "Norrmejerier" means that they do not have a problem with milking cows kept inside in summertime. Because of that they do not have a program for sanctions and they are not planning to make that eider. They also think that the local authority dose a god job with the inspections and the sanctions. "Skånemejerier" says that 5-10% of the milking cows are kept inside all summer. "Arla" is aware that not all milking cows are turned out on pasture. All three dairies agree that the selling will reduce if the cows are not turned out on pasture. It is very impotent for the consumers that the cows are kept out in the summer time. I called 10 milk producers and asked questions about pasture. My conclusion is that al the farmers are turning the cows to pasture but not all of the cows and not everyday. Five of the farms turned out the cows to pasture every day. One has exemption. Three of the farms turned out 50% of the cows to pasture and one turn out 1/3 of the cows. The investigation show that four out of ten farmers will not turn their milking cows on pasture if the demands changes. Two of the farmers would turn out the cows, but not in the same extent. 5 The consumers thi